Commentary Literature of Hadith Science (Content, Causes of Emergence and Types) - Shirinov, Rufat (Scholarya Demo Journal of Ruby, 2019)
Hadiths are the second major sources of Islam after the Holy Quran. The need for hadiths is unquestionable in terms of understanding the commands of the Qur’an and purpose of Islam. Considering this fact, estimable activities have been carried out since the Prophet’s time to make the hadiths more understandable. Commentary studies also emerged as a result of this need. It is possible to come across commentary stuides in various fields of Islam. This article provides an overview of the commentary studies and phases of its emergence in the hadith area. The commentary studies in the hadith area were initially reflected in various lexical explanations. These works were called Qaribul-hadith. From the fourth century the period of collection and classification of commentary works started in the hadith literature. Commentary works are mainly written on Imam Malik’s Muvatta and the work which is known as Kutub al-Sittah in Hadith literature. The main subject of commentary studies is hadith and scholars addressed to this issue to respond to the needs of society, command people from the hadiths, guide them in understanding the Qur’an, explain the sophisticated parts of the narration and to preserve hadith from synicism of some insidious people. When studying the general context of the commentaries, the following points are observed: to cite ayah if it concerns the content of the hadith, consider other narrations around the subject, mention sabab-vurud (the reason of its emergence), command on the idea and fiqh, explain contradictory narrations, address differences in the narrations, emphasize sectarian beliefs and other issues. Various studies started since the Prophet’s time to understand hadiths accurately and this necessity remains relevant in all periods. Changes in society and the mindset of people give impetus to this need. To that end, there is a need for reinterpretation of hadiths at any time, based on the demands of the period without deviating from the main goal of it. Furthermore, it is important to read hadith on the basis of interpretations without moving away from the ultimate goal.